Femur biometry, densitometry and chemical composition from Moxoto goats supplemented with concentrate in a semiarid region - Araujo, M. J.; Medeiros, A. N.; Teixeira, I. A. M. A. [UNESP]; Costa, R. G.; Baraldi-Artoni, Silvana Martinez [UNESP]; Marques, C. A. T.; Resende, Kleber Tomás de [UNESP] (Elsevier B.V., 2011)
The aim of study was to investigate if different intake levels of concentrate (supplementation levels) would have an influence on chemical composition, biometric aspects and bone mineral density (BMD) of femurs from Moxoto growing goats in the Brazilian semiarid region. Thirty-two castrated kids (15.69 +/- 0.78 kg initial BW) were used allocated randomly to one of the four levels of supplementation (SL) (treatments groups: 0: 5; 10 and 15 g/kg BW). When the animals of treatment group 15 g/kg BW reached 25 kg BW, the animals in the others treatments groups were also slaughtered. The increase SL resulted in linear increase (P<0.001) in the performance of animals as well as in fresh and dry weight of the femur and decrease of relative weight of the femur. The dry matter contents (g/kg) of femur increased linearly, however, the amounts of MM, ether extract, Ca, P. Mg, Na and K were not affected by the treatments. The values found in this study ranged from 134.84 to 155.90g of Ca, 48.14 to 55.95g of P. 1.69 to 1.87g of Mg, 2.87 to 3.24g of Na and 1.42 to 1.61 g of K/kg of bone in natura for animals with smaller and higher slaughter weight, respectively. The biometric and densitometric variables increased linearly with increasing treatments, except for the thickness of the sponge layer of the proximal and distal epiphysis and BMD measured in the distal epiphysis. The supplementation with concentrate did not affect the chemical composition of the femur, although it has positively influenced the structure and the bone mineral density. A BMD estimated via radiographic bone aluminum equivalent did not have correspondence with bone mineral content measured chemically. (C) 2011 Elsevier BM. All rights reserved.
Keywords: Bone mineral density; Indigenous goat; Mineral; Supplementation